Forage-Yield and Nutrient Quality of New Brown Midrib (BMR) Mutant Lines of Sorghum - Wahyono, T.; Indriatama, W. M.; Sasongko, W. T.; Shafira, E. N.; Hidayat, T. F.; Widodo, S.; Widiawati, Y.; Rofiq, M. N.; Anggraeny, Y. N.; Kurniawati, A.; Dasumiati (Tropical Animal Science Journal, 2023)
The objective of this study was to evaluate the yield, nutrient profile and in vitro digestibility of new BMR mutant lines of sorghum in Indonesia. These mutant lines were GH2.1, GH2.2, GH2.3, GH4.1, GH4.2, GH4.3 and GH4.4. One sorghum mutant line (CTY) and two national sorghum varieties (Super 1 and Bioguma) were also evaluated as controls. In vitro digestibility and rumen fermentation were measured using Ankom Daisy Fermenter and Hohenheim gas test methods, respectively. In vitro measurement consisted of ten treatments with five replications following a completely randomized design. The highest stem sugar content was found in Bioguma (11.22%) and GH4.4 (9.32%) (p